2023
DOI: 10.1002/nop2.1631
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' healing presence: A panacea for the comfort of acute coronary syndrome patients in CCU, A qualitative study

Abstract: Aim The study aimed to explain the acute coronary syndrome (ACS) patients' perception of the nurse's healing presence in their comfort in the critical care unit. Design This descriptive qualitative study was conducted from December 2020 to September 2021. Methods Twenty‐seven ACS patients were purposively selected from a cardiovascular university Hospital, Iran. Data were collected through semi‐structured interviews (45–60 min). Data analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The client's objectives were delineated and prioritized in accordance with King's theory, leading to a successful treatment trajectory. Evaluation outcomes revealed the client's adjustment of daily activities and attainment of set goals (23,24). In Khalili et al's study, the nursing process was executed for a teenage patient grappling with hyperglycemia using King's goal achievement model.…”
Section: Discussionmentioning
confidence: 99%
“…The client's objectives were delineated and prioritized in accordance with King's theory, leading to a successful treatment trajectory. Evaluation outcomes revealed the client's adjustment of daily activities and attainment of set goals (23,24). In Khalili et al's study, the nursing process was executed for a teenage patient grappling with hyperglycemia using King's goal achievement model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients should be involved in health management planning decisions, effects, and evaluations. In particular, patient-centered health care should be planned based on patients' opinions, needs, and preferences to allow them to take control of their health (18). However, studies have shown that patients believe that nurses are only responsible for their control, and their role in developing preventive behaviors is relatively passive (19).…”
Section: Discussionmentioning
confidence: 99%